Caffeoylquinic Acid-Rich Extract of Aster glehni F. Schmidt Ameliorates Nonalcoholic Fatty Liver through the Regulation of PPAR delta and Adiponectin in ApoE KO Mice - Lee, Yong-Jik; Jang, Yoo-Na; Han, Yoon-Mi; Kim, Hyun-Min; Jeong, Jong-Min; Son, Min Jeoung; Jin, Chang Bae; Kim, Hyoung Ja; Seo, Hong Seog (HINDAWI LTD, 2017)
Aster glehni is well known for its therapeutic properties. This study was performed to investigate the effects of A. glehni on nonalcoholic fatty liver disease (NAFLD) in atherosclerotic condition, by determining the levels of biomarkers related to lipid metabolism and inflammation in serum, liver, and adipose tissue. Body and abdominal adipose tissue weights and serum triglyceride level decreased in all groups treated with A. glehni. Serum adiponectin concentration and protein levels of peroxisome proliferator-activated receptor delta, 5' adenosine monophosphate-activated protein kinase, acetyl-CoA carboxylase, superoxide dismutase, and PPAR gamma coactivator 1-alpha in liver tissues increased in the groups treated with A. glehni. Conversely, protein levels of ATP citrate lyase, fatty acid synthase, tumor necrosis factor alpha, and 3-hydroxy-3-methylglutaryl-CoA reductase and the concentrations of interleukin 6 and reactive oxygen species decreased upon A. glehni. Triglyceride concentration in the liver was lower in mice treated with A. glehni than in control mice. Lipid accumulation in HepG2 and 3T3-L1 cells decreased upon A. glehni treatment; this effect was suppressed in the presence of the PPAR delta antagonist, GSK0660. Our findings suggest that A. glehni extracts may ameliorate NAFLD through regulation of PPAR delta, adiponectin, and the related subgenes.
Keywords: ACTIVATED PROTEIN-KINASE; ATP-CITRATE LYASE; SKELETAL-MUSCLE; OXIDATIVE STRESS; GENE-EXPRESSION; IN-VITRO; DISEASE; GLUCOSE; ALPHA; ASSOCIATION